Does Operational Transparency Affect Tax Avoidance for Firms Listed at the NSE, Kenya? - Muturi, Paul K.; Cheboi, Josphat; Kemboi, Ambrose (African Journal of Education,Science and Technology (AJEST), 2025)
In the present era of globalization and information society, an essential component and factor of an organization’s sustainability is operational transparency. The openness of information on business activities is a criterion for corporate management culture that determines its relationship with stakeholders. Thus, the purpose of this paper was to examine the impact of operational transparency on tax avoidance, which is a key ingredient of corporate trust. Descriptive and inferential statistics were used and the hypothesis was tested using the fixed effect regression model based on the results of the Hausman test. The study employed a sample of 31 firms listed in the Nairobi Securities Exchange and data for the period 2009-2018. The findings of the study show a negative and significant relationship between operational transparency and tax avoidance which have both managerial and policy implications.